2022
DOI: 10.3390/v14112402
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Compositional Bias in a Commercial Phage Display Peptide Library by Next-Generation Sequencing

Abstract: The principal presumption of phage display biopanning is that the naïve library contains an unbiased repertoire of peptides, and thus, the enriched variants derive from the affinity selection of an entirely random peptide pool. In the current study, we utilized deep sequencing to characterize the widely used Ph.DTM-12 phage display peptide library (New England Biolabs). The next-generation sequencing (NGS) data indicated the presence of stop codons and a high abundance of wild-type clones in the naïve library,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…To achieve this purpose, a sequencing platform capable of rigorous characterization of the composition and diversity of the peptide pool is crucial. High-throughput sequencing has been found to be suited for the analysis of the sequence composition and inherent diversity of phage display libraries [ 20 , 31 ]. In the current work, we made a side-by-side comparison of the capacity of two NGS platforms with different depths of sequencing in characterizing the composition and diversity of a phage display peptide library.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To achieve this purpose, a sequencing platform capable of rigorous characterization of the composition and diversity of the peptide pool is crucial. High-throughput sequencing has been found to be suited for the analysis of the sequence composition and inherent diversity of phage display libraries [ 20 , 31 ]. In the current work, we made a side-by-side comparison of the capacity of two NGS platforms with different depths of sequencing in characterizing the composition and diversity of a phage display peptide library.…”
Section: Discussionmentioning
confidence: 99%
“…The available diversity is calculated by titration of amplified phages after electroporation of the library into the host bacterium. Our previous report indicated that the diversity of the library (used in the current work) can be even lower due to the presence of stop codons, frameshifts, and clones without insert in the naïve library [ 20 ]. Consistent with this, the real diversity of phage display peptide libraries is expected to be within the range of 10 8 –10 9 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations